Verbal Persuasion as a Correlate of Adolescents’ Self-efficacy in Utilizing Sexual and Reproductive Health Services in Tanzania (Tanzania Journal for Population studies and Development, 2025)
The study investigated verbal persuasion as a correlate of adolescents’ self-efficacy in utilizing sexual and reproductive health services in secondary schools, in Tanzania. Specifically, it sought to determine the relationship between adolescents’ verbal persuasion and the utilization of sexual and reproductive health services. The study employed a quantitative research approach and a correlational research design. Using stratified and simple random sampling, the it drew a sample of 552 secondary school adolescents from Katavi and Njombe regions. The study used questionnaires to collect data; and then used the SPSS, version 25, to analyse it. Descriptive analyses were performed across four demographic characteristics, namely, gender, age, class level, and type of school. Additionally, inferential statistics, including Spearman’s correlation coefficient, helped determine the relationship between verbal persuasion and the utilization of SRHS in terms of condom use and HIV testing and counselling among secondary schools students. The results revealed a weak, positive and significant relationship between verbal persuasion and adolescents’ condom use (r = .266, p-value